2018
DOI: 10.3920/cep170030
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of bra concerns and barriers to participation in horse riding

Abstract: Horse riding is a female-dominated sport where participation levels are declining. The influence of the breast on participation levels and current satisfaction with bras for this activity is unknown. This study aimed to investigate bra concerns and breast-related barriers to participation in horse riding. A 6-part, 32 question online survey was completed by 1,324 females who participated in horse riding. Descriptive and chi-squared analyses were utilised; inductive content analysis was completed to analyse qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…Most UK (64.1%) and US (65.6%) participants had never been professionally fitted for a sports bra, which corresponds to previous UK research (Brown et al, 2014;Burbage and Cameron, 2018). In contrast, over half of Chinese participants were professionally fitted for a sports bra in the last month, or last three months.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Most UK (64.1%) and US (65.6%) participants had never been professionally fitted for a sports bra, which corresponds to previous UK research (Brown et al, 2014;Burbage and Cameron, 2018). In contrast, over half of Chinese participants were professionally fitted for a sports bra in the last month, or last three months.…”
Section: Discussionsupporting
confidence: 58%
“…Larger-breasted women are reported to experience more bra fit issues due to the large range of breast mass and volume within a bra size making identifying an appropriate bra more challenging (McGhee et al, 2013). Rubbing and chaffing, shoulder straps digging in, upper body pain, and poor posture were bra issues experienced significantly more frequently by participants with larger breasts compared to those with smaller breasts (Brown et al, 2014;Burbage and Cameron, 2018). Furthermore, Brown et al (2014) reported that sports bra use was more frequent and perceived as more important in larger-breasted women (≥D cup).…”
Section: Introductionmentioning
confidence: 99%
“…Chi-squared tests of independence using two-sided Fisher's exact test (FET) (expected frequencies 5) (Field 2013) were used to determine associations between bra cup size and BMI, breast pain, and frequency of bra fit issues during BT. Bra cup size was split into 'small' (AA-C cup) and 'large' (!D cup) for the purpose of the statistical analysis (Burbage and Cameron 2018). However, it is acknowledged that this does not account for band size of the recruits and is therefore a crude measure of breast size and estimate of breast volume.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, certain sports bras may be more ideal for particular sports or movement patterns. Research has shown that with different movement patterns, such as running and jumping, breast motion can be different, so different sports bras may be needed to provide optimal support for different activities [ 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]. A few companies have created guidelines for sports bra fittings [ 37 , 38 ] and there is a web-based fitting program from an academic center well known for its research in this area [ 39 ], but hands-on fittings may only offered in certain areas, which can limit access to proper fit and education around optimal fit.…”
Section: Discussion and Limitationsmentioning
confidence: 99%